2016
DOI: 10.1097/01.aoa.0000489467.69038.9d
|View full text |Cite
|
Sign up to set email alerts
|

Shared Genetic Predisposition in Peripartum and Dilated Cardiomyopathies

Abstract: (N Engl J Med. 2016;374:233–241) It is possible that peripartum cardiomyopathy is influenced by genetic factors, though this remains unclear. Similar to idiopathic dilated cardiomyopathy, this disease is associated with decreased systolic function, enlarged cardiac dimensions, and nonspecific histologic findings. These similarities are significant in that idiopathic dilated cardiomyopathy has been shown to be caused by a number of gene mutations. The authors of this study sequenced the DNA of 172 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
110
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(112 citation statements)
references
References 0 publications
2
110
0
Order By: Relevance
“…The prevalence of truncating variants (26 of 172: 15%) was significantly higher than that in a reference population (4.7%), but was similar to that in a cohort of patients with DCM (17%). 28 Interestingly, the prevalence of variants was the same in the USA, Germany and Japan, and even among a cohort of patients who underwent either cardiac transplantation or placement of a LV assist device. Two-thirds of the identified truncating variants were in TTN.…”
Section: Ppcm and Dcmmentioning
confidence: 95%
See 1 more Smart Citation
“…The prevalence of truncating variants (26 of 172: 15%) was significantly higher than that in a reference population (4.7%), but was similar to that in a cohort of patients with DCM (17%). 28 Interestingly, the prevalence of variants was the same in the USA, Germany and Japan, and even among a cohort of patients who underwent either cardiac transplantation or placement of a LV assist device. Two-thirds of the identified truncating variants were in TTN.…”
Section: Ppcm and Dcmmentioning
confidence: 95%
“…29 In a clinically well-characterized cohort of 83 women with PPCM, the presence of TTN truncating variants was significantly correlated with a lower LVEF at 1-year followup. 28 weight gain, resemble those complained about by normal peripartum women, which makes it very difficult to diagnose PPCM. At the same time, a low level of awareness and failure to routinely think of a cardiac cause for these symptoms are related to delayed diagnosis in many cases.…”
Section: Ppcm and Dcmmentioning
confidence: 99%
“…The observed geographical variation suggests potential genetic predisposition, with known familial clustering providing further support to this notion. 7 There appears to be an association with the parathyroid hormone-like hormone ( PTHLH ) gene, which modulates vascular homeostasis via calcium channel agonisation. 8 Moreover, the TTN gene, which encodes the sarcomeric protein titin, has also been implicated in pathogenesis.…”
Section: Pathophysiologymentioning
confidence: 99%
“…8 Moreover, the TTN gene, which encodes the sarcomeric protein titin, has also been implicated in pathogenesis. 9 A novel hypothesis relates to excess prolactin production, which is associated with enhanced intravascular volumes, suppressed response to angiotensin and increased circulating erythropoietin levels. 10 An exploration of unifying mechanisms is provided later in this article and is summarised in Fig 1 . Alternate suggestions indicate that PPCM occurs secondary to haemodynamic perturbations in the context of pregnancy.…”
Section: Pathophysiologymentioning
confidence: 99%
“…63,64 Recently, a large study on 172 PPCMP patients, showed a prevalence of truncating variants (especially in the Titin gene) similar to DCM patients, suggesting that these variants may predispose to the condition. 65 Myocarditis appears to be the main pathophysiological mechanism in PPCMP. A 76% incidence of myocarditis at myocardial biopsy was reported in a study on a large number of patients with PPCMP.…”
Section: Peripartum Cardiomyopathymentioning
confidence: 99%